Pengaruh Pola Asuh Permisif Orangtua Dalam Perkembangan Kreativitas Anak di Desa Kakorotan Kecamatan Nanusa Kabupaten Talaud - Djony . M Saroinsong (Peneliti.net, 2023)
The aim of this research is to increase creativity in children in Kakorotan village, Kec. Nanusa District. Talaud through good and correct permissive parenting. The research method used is qualitative research, which is research used to examine the condition of natural objects where the researcher is the key instrument. Research location: Kakorotan Village, Nanusa District, Kep Regency. Talaud The results of the research show that permissive parenting is: (1) Parents focus their attention on their main job as fishermen and housewives, thereby neglecting the responsibility of guiding children, resulting in children dropping out of school, (2) Decision making for children's educational activities is completely left to the children. outside parental supervision, and (3) The number of families who implement permissive parenting in Kakorotan village is quite large, but the focus of the research is two families.